L’atelier de Marko. Énergie, intention, ambiance et technique(s) : un dessinateur de bande dessinée à l’œuvre - Isabelle Rivoal; Marc Armspach (Images du Travail, Travail des Images)
How is it possible to respond to the epistemological project delineated by Etienne Souriau : appraising the work of art as establishing rather than designing – establishing here meaning and involving the incessant questioning of the agent by the work to be done ? How to observe and ethnography the establishment, the ordeal which consists in renouncing, erasing, resuming, repeating ? From a close observation of a cartoonist at his graphic table, the article confirms Souriau's intuition on the importance of trial and error in the search for the accuracy of the sketch. It describes the creator's engagement in the form to realize and analyzes the material and cognitive conditions by which the drawing finds its form. Finally, it reports on what is finally established by the designer at his work table : a strip, a page... but also a personal graphic style which is the quest for the professional comic book designer.